Drowning incidents precipitated by unusual causes (DIPUCs): A narrative review of their diagnoses, evaluation and management - Kevin M. Duignan; Hannah Luu; João H. Delgado; Shawn London; Richard M. Ratzan (Resuscitation Plus, 2024)
Drowning is a cause of significant morbidity and mortality worldwide. In most circumstances, the proximate cause is attributable to human factors, such as inexperience, fatigue, intoxication, or hazardous water conditions. The phenomenon of drowning incidents precipitated by unusual circumstances (DIPUCs) – either fatal or nonfatal – involving otherwise healthy individuals under generally safe conditions has not been comprehensively addressed in the medical and drowning literature to date. In this review, we discuss etiologies of DIPUCs, diagnostic clues, suggested workup, suggested postmortem testing, and implications for surviving patients and families. Identifying the cause of a drowning incident can be extremely challenging for the initially treating physician, relying perforce on historical context, environmental clues, physical exam, medical history, eyewitness accounts or video recordings. If no clear explanation for a drowning incident emerges despite a thorough investigation, clinicians should consider some of the less common diagnoses we describe in this paper, and, when appropriate, refer for an autopsy with postmortem molecular genetic testing. While time-consuming, these efforts can prove life-saving for some non-fatal drowning victims and the families of all victims of DIPUCs.